Proton pump inhibitors and osteoporosis. Issue 4 (July 2016) - Andersen, Bjarne Nesgaard; Johansen, Per Birger; Abrahamsen, Bo
Abstract : Purpose of review: The purpose of the review is to provide an update on recent advances in the evidence based on proton pump inhibitors (PPI) as a possible cause of osteoporosis and osteoporotic fractures. This review focuses, in particular, on new studies published in the last 18 months and a discussion of these findings and how this has influenced our understanding of this association, the clinical impact and the underlying pathophysiology. Recent findings: New studies have further strengthened existing evidence linking use of PPIs to osteoporosis. Short-term use does not appear to pose a lower risk than long-term use. There is a continued lack of conclusive studies identifying the pathogenesis. Direct effects on calcium absorption or on osteoblast or osteoclast action cannot at present plausibly explain the mechanism. Summary: The use of PPIs is a risk factor for development of osteoporosis and osteoporotic fractures. However, as the direct pathogenesis remains unclear, specific points of intervention are lacking, other than being vigilant in regard to the indication for prescribing PPIs and to use the lowest effective dose where PPIs cannot be avoided.